2022
DOI: 10.1136/bmjopen-2020-048314
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of community-dwelling adults regarding advance care planning in Malaysia: a cross-sectional study

Abstract: ObjectivesThis study aimed to assess the knowledge, attitude and practice (KAP) among community-dwelling adults in Malaysia regarding advance care planning (ACP), and its associated factors.DesignThis cross-sectional study was conducted from July–September 2018.SettingThis study was conducted at the University Malaya Medical Centre, Kuala Lumpur, Malaysia.ParticipantsWe recruited community-dwelling adults (ambulatory care patients or their accompanying persons) who were ≥21 years old and able to understand Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 69 publications
(136 reference statements)
3
2
0
Order By: Relevance
“…Despite these aspects of literacy, the results of the study showed that attitudes toward ADs were mostly positive, which agreed with the findings of other studies [18,27,[47][48][49]56,58,[75][76][77]. However, there were also negative and even neutral attitudes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite these aspects of literacy, the results of the study showed that attitudes toward ADs were mostly positive, which agreed with the findings of other studies [18,27,[47][48][49]56,58,[75][76][77]. However, there were also negative and even neutral attitudes.…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained in relation to literacy of the sample on the ADs, which revealed a lack of knowledge on the subject, were consistent with the findings of other studies [20,27,[41][42][43][44][45][46][47][48][49]. A systematic review of the literature published from 1994 to 2016, revealed a low level of knowledge about ADs [19].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it can be assumed that the overall attitude toward the health care system of the participants in this study was less likely to distort their answers to the questionnaire. This is also supported by that the trust in the health care system in each country, as investigated in previous studies [ 74 ], differs from the international awareness of ACP or HPC [ 34 – 38 ].…”
Section: Discussionsupporting
confidence: 56%
“…Comparing awareness across countries is challenging because of differences in health care system, legal implementation, and public insurance coverage. Nevertheless, ACP awareness investigated in our study was relatively lower than those of United States and European countries (40–90%) [ 34 – 36 ], but similar to or higher than those of Asian countries (3–36%) [ 37 , 38 ]. Previous studies conducted prior to the enactment of the Act on Life-Sustaining Treatment Decisions found that Koreans’ awareness of ACP ranged from 10 to 16% [ 31 , 37 ].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation